Mechanical and biological properties of 3D printed bone tissue engineering scaffolds - Wang, Mingxuan; Xu, Yunpeng; Cao, Luoxi; Xiong, Le; Shang, Depeng; Cong, Yang; Zhao, Dan; Wei, Xiaowei; Li, Junlei; Fu, Dapeng; Lian, Haoyi; Zhao, Zhenhua (Frontiers in Bioengineering and Biotechnology, 2025)
Bone defects have historically represented a significant challenge in clinical practice, with traditional surgical intervention remaining the gold standard for their management. However, due to the problem of the origin of autologous and allogeneic bone and the complex and diverse bone defects, traditional surgical methods sometimes cannot meet the treatment needs and expectations of patients. The development of bone tissue engineering and 3D printing technology provides new ideas for bone defect repair. Ideal bioscaffold materials must have good mechanical properties, biocompatibility, osteoinduction and bone conduction capabilities. Additionally, factors such as degradation rate, appropriate porosity and a sustained antibacterial effect must be taken into account. The combination of 3D printing technology and synthetic composite biomaterial scaffolds has become a well-established approach in the treatment of complex bone defects, offering innovative solutions for bone defect repair. The combined application of seed cells, signalling factors and biological scaffolds is also beneficial to improve the therapeutic effect of complex bone defects. This article will therefore examine some of the most commonly used 3D printing technologies for biological scaffolds and the most prevalent bioscaffold materials suitable for 3D printing. An analysis will be conducted on the mechanical and biological properties of these materials to elucidate their respective advantages and limitations.